Social Responsibility from an Islamic Perspective And Their Positive Impact on Organizations - Shmailan, Abdulwahab (The Arab Journal of Administration, 2018)
The aim of the research is to define social responsibility, to show its impact on society and to highlight the importance of social responsibility in the world of business management and companies. It also provides a feasibility study to activate the role of social responsibility to bring about the social progress of individuals and companies, and to clarify the effective impact of social responsibility from an Islamic perspective on both individuals and companies. The social responsibility is a religious appeal, urged by our true religion for its importance, recent studies and pioneering experiments emphasize the need to activate the role of social responsibility, and there is a strong relationship between activating the role of social responsibility and the success of institutions and companies. The study showed that social responsibility is a religious requirement since the beginning of Islam and not the birth of the day as described in this research and confirm that from the Quranic verses and the Prophet Mohammd (SAW). There is a clear success for some companies that have activated the social responsibility. This paper encourages governmental organizations, private organizations and society as well as countries to pay attention to social responsibility and encourage research and academic studies.